(untitled) (Italian Journal of Public Health, 2009)
Dear editor, in the year 2009, a series of disasters have occurred. Abruzzi: 293 fatalities and 1500 wounded people. Viareggio: 29 fatalities and 30 wounded people. Messina: 35 fatalities and 40 wounded people. Samoa Island: more than 1000 dead and more than 700 wounded people. These are just some of the tragic events that have occurred in 2009 over a period of eight months. Catastrophes can cause a high number of victims. During large scale emergencies caused by either natural disasters (earthquakes, avalanches, floods, tornados) or human acts (conflagrations, terroristic acts, etc) the first aid philosophy is to recognize the need for triage so to help foremost the individuals with more severe injuries. In Italy, the so called advanced medical structure (Postazione Medica Avanzata , PMA) is assigned to triage and stabilize patients’ vital signs, and then coordinate the transfer of these patients to operational tertiary care centers. The PMA staff includes physicians and nurses. There are two types of PMAs. The PMA level I is a motorized agile health care delivery unit that has the ability to assist at least 10 patients, and operate thanks to one or more vehicles or a transportation system that will allow the PMA unit to travel and move to where it is most needed. The PMA level II is a more complex hospital camp-like structure that is able to provide assistance for 50 patients over a period of 72 hours.